Sustainable Development: Memorizing the Quran Using the Takrir Method - Asikin Kakoh, Nur; Helminswita, Kosra; Zulmasri, Zulmasri; Masyhudi, Fauza (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
This research is based on several symptoms that point to the need to improve the ability to read and memorize short surahs in elementary schools. There are still many students who are not yet able to read the Quran properly and correctly, there are still students who are not yet able to read the Alquran. The aim of this research is to find out about planning, implementation and improving the results of the ability to memorize short verses using the tahrir method in elementary schools in Indonesia. This type of research is Classroom Action Research, research carried out in elementary schools. The data source in this research is elementary school students, totaling 14 students. Data collection techniques are observation, documentation and test techniques. The data analysis technique consists of four steps, namely the first planning stage, implementation stage, observation and reflection stage. The results of the research show that learning planning uses the assessment method, namely by preparing learning implementation plans, teaching materials about length measuring instruments, preparing observation sheets, and supporting tools needed in the learning process. The second learning implementation using the inquiry method was carried out in two cycles with four meetings. The three research results showed an increase in the average score of students in cycle I, namely 63.93, increasing to 83.17 in cycle II using the assessment method with a percentage of completeness in the ability to memorize short verses for students from cycle I of 5 people (35.71 %) increased to 13 people (92.86%) in cycle II.